2011
DOI: 10.1002/adfm.201101303
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Interfacial Phenomena to Program the Release Properties of Hollow Microcapsules

Abstract: The generation of near‐infrared (NIR)‐sensitive microcapsules is presented and it is demonstrated that the release properties of these microcapsules can be tailored by controlling their morphology. A biocompatible polymer, poly(DL‐lactic‐co‐glycolic)acid (PLGA) is used to form hollow microcapsules from monodisperse water‐in‐oil‐in‐water (W/O/W) double emulsions. Both the composition of PLGA and the oil phase of W/O/W double emulsions significantly affect the morphology of the subsequently formed microcapsules.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
84
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 42 publications
0
84
0
Order By: Relevance
“…Analogous behaviors of inner core protrusion from W/O/W double emulsions have been observed when diblock copolymers, random copolymers and phospholipids were dissolved in the middle phase of W/O/W double emulsions. [43][44][45][46] However, a complete separation of the inner core from the oil phase has been seldom observed. 44,47 The interfacial complexation of bPEI and PAA leads to the ionization of functional groups of the two polymers, rendering the complex layer hydrophilic and more importantly oleophobic.…”
Section: Generation and Characterization Of (Paa/bpei) Nice Microcapsulementioning
confidence: 98%
“…Analogous behaviors of inner core protrusion from W/O/W double emulsions have been observed when diblock copolymers, random copolymers and phospholipids were dissolved in the middle phase of W/O/W double emulsions. [43][44][45][46] However, a complete separation of the inner core from the oil phase has been seldom observed. 44,47 The interfacial complexation of bPEI and PAA leads to the ionization of functional groups of the two polymers, rendering the complex layer hydrophilic and more importantly oleophobic.…”
Section: Generation and Characterization Of (Paa/bpei) Nice Microcapsulementioning
confidence: 98%
“…West and co-workers [22] suggested that the permeability changes of the N-isopropylacrylamide/acrylamide capsules walls containing gold nanoparticles, upon laser irradiation, could be useful in insulin therapy. Recently, Lee et al [23] prepared microcapsules of poly(DL-lactic-co-glycolic acid) (PLGA) containing gold nanorods by using water-oil-water (W/O/W) double emulsions. Upon laser irradiation, the nanorods generated heat via a photothermal effect, and as a result, the membrane became more permeable above the glass transition temperature of the PLGA, thereby providing remote control release of the active material.…”
Section: Microcapsules Containing Silver and Gold Particlesmentioning
confidence: 99%
“…[19]). Double emulsion combined with a solvent evaporation technique was often used for preparation of microspheres both in batch (Rosca et al [20]) and microfluidic arrangement (Lee et al [21]). Preparation of nanoparticles was also investigated but resulting particles typically had irregular shape (Fonte et al [22], Zambaux et al [23]).…”
Section: Introductionmentioning
confidence: 99%